Emulation of Energy Scheduling for an Agriculture Irrigation System Considering Field Data - Abrishambaf, Omid (2021)
As the global population is daily soaring, the need for water and energy is also increasing. This makes the role of the agriculture sector more tangible. Water and energy efficiency in this sector is still very low, and the need for smart management and strategic planning are obvious. This paper proposes an autonomous approach to increase the efficiency of energy and water consumption in the agriculture irrigation process. The model contains local renewable energy resources to supply the irrigation electricity demand. In the previous works developed by the authors, the irrigation scheduling had been performed by a decision tree approach. however, in this paper, the model schedules irrigation according to the realtime field data as well as the availability of the local resources to minimize operational costs. The system also includes a laboratory demonstration to test the scheduling process under practical challenges. A case study is also shown to validate the model, and its results show a gap between expected and real results. Nevertheless, the results proved the functionality and applicability of the proposed model.